APLIKASI PEMESANAN MAKANAN DAN MINUMAN PADA DECOST RESTO MUARA JAMBI BERBASIS WEB: Applications;Decost Resto;Mysql;Menu Data;Web. - Nurjani, Yeni; Yuspita, Rika (LP2M Universitas Nurdin Hamzah, 2021)
Decost Resto is a business engaged in the sale of food and beverages in Muara Jambi. Currently Decost Resto wants to increase its sales level by expanding its sales outside Mara Jambi to seek greater sales profits. The purpose of this research is to build a web-based computerized sales application which includes product catalogs, sales transactions and reports that are expected to increase sales turnover of food and beverages. This application is built using the PHP programming language and MySQL database. Input in this application is in the form of menu data, order data, transaction data and sales report data. Process data in this application are in the form of menu data input processes, order data input processes, transaction input processes, sales report data input processes. The output of this application is a sales report. The results of this study are a web - based sales application that can help Decost Resto make it easier to order food and drinks more widely and make it easier to make sales reports.